Predictors of overall mortality among people living with HIV/AIDS in Brazil, 2007-2015. (13th November 2019) - Santos, M E; Ribeiro, R A; Protopopescu, C; Nishimwe, M; Yaya, I; Carrieri, M P; Araujo, W N
Abstract: Background: In Brazil there are 926, 742 people living with HIV/AIDS (PLWHA). Despite the introduction of antiretroviral therapy (ART) in 1996 and treatment for all in 2014, mortality has increased in some regions. This study aimed to estimate the factors associated with overall mortality in PLWHA to recommend public health actions. Methods: We studied PLWHA aged ≥18 years old, followed-up from 2007 to 2015 in the universal health system in Brazil. We used a national database (disease reporting, laboratory tests, ART and death notifications). Kaplan-Meier method and Cox model were used in survival analysis. The outcome was all-cause deaths. The explanatory variables measured at baseline were sociodemographic characteristics, HIV transmission mode and coinfections by hepatitis B (HBV) and C (HCV). The time-varying variables were CD4 cell count, viral load (VL) and ART status. Results: Study population (n = 411, 281) was mainly male (61%), under 40 years old (61%), Caucasian (37%), with basic education (43%), heterosexual HIV-infection mode (41%), resident in Southeast region (48%). The co-infection rate was 2.5% for HCV, and 1.4% for HBV. Median time to ART initiation was 83 days. During the follow-up period (median: 4 years), 61, 757 deaths occurred (6% HCV-coinfected and 2% HBV-coinfected). The global mortality rate was 3.44 [95% confidence interval: 3.42-3.47] per 100 person-years (PY) during 1, 793, 417 PY. The factors associated with increased mortality in multivariable analyses were male gender, age over 40, non-Caucasian race, HIV infection by drug use, resident in North, Northeast and South regions, HCV and HBV coinfection, VL ≥ 200 copies/mL and starting ART with CD4<200 cells/mm3. Conclusions: Although PLWHA start ART in less than 3 months after the beginning of follow-up, there is still late treatment (at CD4<200 cells/mm3). Screening should target all populations regardless of risk group. Coinfected individuals should also be early treated for HCV and HBV infections. Key messages: The results of our study show that all populations should be target for HIV screening regardless of risk group. PLWHA coinfected with hepatitis B and hepatitis C should be also early treated for hepatitis coinfections.